Turkey and Some EU Countries’ Economic Performance Analysis with Multi-criteria Decision Making Methods: Promethee GAIA Application - Karahan, Mehmet; Çetintaş, Fatma; Karahan, Merve Sinem (Springer Science and Business Media Deutschland GmbH, 2021)
The economic performance of countries can be compared with various methods and the results obtained from these comparisons are accepted as the economic levels of the countries covering certain periods. Since the ranking or comparison of countries according to their economic performances can be made according to many criteria, mathematical methods are needed in which all criteria are taken into consideration in such performance measurements. Multi-criteria decision-making (MCDM) methods have the ability to alternate sorting, to choose and classify alternatives with the results frequently used and obtained in such comparisons. They are widely used in economic comparisons, in decision problems where many alternatives and criteria are evaluated. Promethee method, which is one of the newest MCDM methods developed to select the best alternative within the framework of determined criteria, is one of the most effective and easiest methods for solving such problems. In the study, 10 EU countries, Turkey and the intended method of measuring the economic performance of Promethee 2018, five key economic criteria were used in this measurement. Determining the performance level of the countries covered in the study, Turkey’s uncovering of inadequacy or superiority of some in comparison with EU countries is very important in the sense. According to the Promethee I partial ranking results obtained from the study; Luxembourg has a more dominant and partial priority than other countries. According to the Slovakia-Ireland Likewise, it is more prevalent than Turkey and the Netherlands. According to the ranking of the provinces that showed clear superiority in the full rankings of Promethee II; While the weight of Luxembourg is positive, the weight of Slovakia is negative. Luxembourg ranks first among the countries covered by the analysis, having the highest net Phi value. These countries respectively, Slovakia, Ireland, Belgium, Lithuania, Slovenia, Hungary, Estonia, Turkey, the Netherlands and Latvia are to follow. The Quality value, which represents the quality of the Promethee GAIA measurement, was calculated as 86% for this study. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
International Symposium for Production Research, ISPR 2020 -- 24 September 2020 through 26 September 2020 -- Antalya -- 250869
Keywords: Economic performance; GAIA; MCDM; Performance management; Promethee